FACTORS AFFECTING ECO-TOURISM DEVELOPMENT IN ZANZIBAR - Kombo, Dr. Ibun (IJRDO - Journal of Social Science and Humanities Research, 2016)
This paper examined and analyzed tourism development in Zanzibar, concentrating on areas of Unguja Island. More specifically, it has examined three aspects, namely, inhibiting factors for eco-tourism development, favouring factors and potential sites for eco-tourism development. Both qualitative and quantitative data collection methods were used to explore factors affecting eco-tourism development in Zanzibar. Structured questionnaires with both open and closed ended questions were administered to all respondents involved in the study. Interviews and Focus Group Discussions (FGDs) were organized in order to compare and confirm the respondents’ responses arising from the questionnaire survey. Overall study findings have revealed that, eco- tourism is facing several challenges. Furthermore, the study has revealed that tourism industry has lots of potentials that can be developed for eco-tourism which can enable to reach the aim of tourism policy in Zanzibar. The government should develop special program and agenda for eco-tourism. The government is also required to have a special organ or commission responsible for implementing eco-tourism program campaigns.